THE EFFECT OF SHOPPING ORIENTATION ON THRIFT CLOTHING PURCHASING DECISIONS IN PADANG STATE UNIVERSITY STUDENT - Rahmadani, Auwiya; Nurmina (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Thrifts are used goods, both local and imported, that are in a condition suitable for use. Examples of thrift goods that are widely bought and sold are clothes, shoes, bags, electronics or other antique objects. Shopping orientation and purchasing decisions are two of the many factors in purchasing thrift goods. This research aims to see the influence of shopping orientation on the decision to purchase thrift clothing among Padang State University students. This research uses a correlational quantitative design. The sampling technique used was an accidental technique with a population of Padang State University students. The sample in this study amounted to 255 people. Data were analyzed using simple linear regression analysis. The research results show that there is an influence of shopping orientation on the decision to purchase thrift clothing among Padang State University students. It is known that the value of F = 5.956 with a significance level of 0.015 < 0.05. The correlation value (R) is 0.152 and the coefficient of determination (R Square) is 0.023, which means the influence of shopping orientation on purchasing decisions is 2.3%.